A psychological study of children legally removed from parental care - Stricklin, Ann Burns (Department of Psychology, 2023)
The problem of the child who is legally removed from their parental care, although it may only be on a temporary basis, is an enormously expensive undertaking, both in terms of financial and emotional expenditure. In every respect, to all concerned, the event is a painful and tragic one. there have been few studies in other countries relative to the child legally removed from parental care. A careful search of the literature failed to bring to light other studies which were of the same nature as the present study. No studies of a psychological nature had been undertaken in South Africa, thus leaving the practitioner in this country with a limited and uncertain knowledge base from which to work with children requiring protective services